A combination of astragaloside I, levistilide A and calycosin exerts anti-liver fibrosis effects in vitro and in vivo - GUO Tao; LIU Zu-long; ZHAO Qiang; ZHAO Zhi-min; LIU Cheng-hai (Acta Pharmacologica Sinica, 2018)
Liver fibrosis is excessive accumulation of extracellular matrix proteins that results from various chronic liver diseases. Hepatic stellate cells (HSCs) play an essential role in the pathogenesis of liver fibrosis. Danggui Buxue Tang (DBT) is a classic formula of Chinese traditional medicine. We previously showed that DBT could ameliorate liver fibrosis in rats. However, the bioactive components of DBT in the treatment of liver fibrosis remain unknown. In this study we evaluated 14 ingredients from DBT in human hepatic stellate cell line LX-2, and found that astragaloside I (A), levistilide A (L) and calycosin (C) produced synergistic proliferation inhibition on LX-2 cells and TGF-β1-activated LX-2 cells. Thus, we prepared a mixture of them, and named this combination as ALC formula. Using high-content screening and Western blot assay we revealed that the ALC formula significantly reduced the expression of α-SMA and collagen I in LX-2 cells. The in vivo anti-fibrosis effects of ALC formula were evaluated in a liver fibrosis model in C57BL/6 mice established through injection of dimethylnitrosamine (DMN 2 mg/kg, ip) for 4 weeks. In the third week, the mice were injected with ALC formula (astragaloside I 44.21 mg/kg per day, levistilide A 6 mg/kg per day and calycosin 3.45 mg/kg per day; ip) or sorafenib, a positive control drug (6 mg/kg per day, ip) for 2 weeks. We found that administration of the ALC formula markedly decreased collagen deposition, hydroxyproline (Hyp) content and α-SMA expression levels in the liver tissues compared to the model mice. In conclusion, the present study demonstrates for the first time that astragaloside I, levistilide A and calycosin may be the 3 main bioactive components in DBT; their combination exerts anti-liver fibrosis effects in vitro and in vivo.